From a helix to a small cycle: metadynamics-inspired alpha v beta 6 integrin selective ligands - Di Leva, Francesco Saverio; Tomassi, Stefano; Di Maro, Salvatore; Reichart, Florian; Notni, Johannes; Dangi, Abha; Marelli, Udaya Kiran; Brancaccio, Diego; Merlino, Francesco; Wester, Hans-Juergen; Novellino, Ettore; Kessler, Horst; et al. (Angewandte Chemie-International Edition, 2018)
The RGD-recognizing alpha v beta 6 integrin has only recently emerged as a major target for cancer diagnosis and therapy. Thus, the development of selective, low-molecular-weight ligands of this receptor is still in great demand. Here, a metadynamics-driven design strategy allowed us to successfully convert a helical nonapeptide into a cyclic pentapeptide (6) showing remarkable potency and alpha v beta 6 specificity. NMR and docking studies elucidated the reasons for the high affinity and selectivity of this compound, setting the ground for the rational design of new alpha v beta 6-specific small peptides or even peptidomimetics. In vivo PET imaging studies demonstrated the potential use of 6 for medical applications.